The Influence of Historical and Cultural Potential on the Development of Small Historical Towns on the Example of the Concept of Developing a Tourist and Recreational Cluster in Russia, Arkhangelsk Region, the City of Kargopol (Global Journal of Human-Social Science, 2024)
- - - - - -